The measurement of child costs: evidence from Ireland - Olivier Bargain; Olivier Donni; Monnet Benoit Patrick Gbakou (Institute for the Study of Labor (IZA), 2009)
We apply an extension of the Rothbarth approach to estimate the share of household resources accruing to children (i.e., the cost of children) in Ireland. The method also allows us to identify the economies of scale in the household and indifference scales in Lewbel (2003)'s sense. A practical aspect of the present approach is that it does not require price variation. The identification of the children's share requires the observation of adult-specific goods as in the traditional Rothbarth method. We compare our findings to previous results for Ireland.
Keywords: D11; D12; C30; D36; I31; J12; 330; Consumer demand; collective model; sharing rule; cost of children; equivalence scales; indifference scales; Kinder; Kosten; Messung; Haushaltseinkommen; Verbraucherausgaben; Skalenertrag; Theorie; Irland